2004
DOI: 10.5144/0256-4947.2004.189
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cervical smears in a Muslim population

Abstract: BackgroundScreening for cancer of the cervix remains a neglected health care issue in Pakistan. To provide baseline data for future efforts to improve screening, we conducted a retrospective analysis of cervical smears taken in the obstetrics and gynaecological clinics of the Aga Khan University Hospital, Karachi, Pakistan.MethodWe collected data on cervical smear cytology for cervical smears taken from January 1, 1990 to December 31, 1996. We assessed risk factors for dysplasia, including age, age at first ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
0
15
1
Order By: Relevance
“…For counseling young women and for organizing a public health system it is important to know the incidence of cervical intraepithelial lesions in a country. A relatively low prevalence of abnormal smears and cervical cancer has been reported in the Muslim as compared with the Western population [6][7][8][9][10][11][12] . This is most likely related to sexual behavior under Islamic rules [10] , the lack of awareness of cervical cancer risk factors among women, and the low awareness that routine gynecological examinations and Pap smears are essential [11,13,14] .…”
mentioning
confidence: 99%
“…For counseling young women and for organizing a public health system it is important to know the incidence of cervical intraepithelial lesions in a country. A relatively low prevalence of abnormal smears and cervical cancer has been reported in the Muslim as compared with the Western population [6][7][8][9][10][11][12] . This is most likely related to sexual behavior under Islamic rules [10] , the lack of awareness of cervical cancer risk factors among women, and the low awareness that routine gynecological examinations and Pap smears are essential [11,13,14] .…”
mentioning
confidence: 99%
“…4 In another study, conducted at Karachi, Pakistan, cervical smear was taken in 20,995 cervical smears taken in the obstetrics and gynaecological clinics showed 0.71% atypia. 5 Another study conducted in India in which 300 pap smears were taken from patients who attended obstetrics and gynaecology showed cervical epithelial abnormalities in 5% of cases. 6 Every three yearly Pap smear is recommended in women aged 18 to 69 years, who have ever been sexually active.…”
Section: Introductionmentioning
confidence: 99%
“…4 Similarly, studies conducted in Pakistan and India screened both obstetrics and gynaecological patients showed up to 5% of cervical epithetlial abnormalities. 5,6 It means that study conducted in antenatal population showed high incidence of CIN as compared to both obstetrics and gynae patients. These studies indicated that pap smear is not taken regularly in reproductive age groups in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…3 The main risk factor for cervical cancer is infection with human papilloma virus (HPV) types 16,18,31,33,35,42,55,58. HPV types 16 and 18 are the cause of 70% of cervical cancer worldwide while 31 and 45 are the cause of another 10%.…”
Section: Introductionmentioning
confidence: 99%